PENERAPAN MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) UNTUK MENINGKATKAN BERPIKIR HOTS (HIGHER ORDER THINKING SKILL) SISWA DI KELAS VI SD NEGERI 067259 KECAMATAN MEDAN JOHOR - Rumiris Lumban Gaol; Lia Kusuma Sari Br. Bangun; Juli Azmi; Suci Rahmadani Siregar; Lia Lestari; Vina Adelia Sinaga; Evelyn Mine Angelina Br Barus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to improve students' critical thinking by using the CTL (Contextual Teaching And Learning) learning model in the Pancasila education subject. The subjects in this study were 28 grade VI students. The techniques used by researchers in collecting data were observation and tests. This study shows an increase in students' critical thinking from cycle 1 to cycle II, namely from 50% to 85%, then from the analysis of the results of the learning evaluation of cycle II, the learning completion reached 85%. So, by applying the CTL (Contextual Teaching And Learning) model, the critical thinking skills of grade VI students were able to increase and experience student learning completion reaching the success indicator, namely 85%.